2021
DOI: 10.1508/cytologia.86.133
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Study of <i>Begonia</i> Sect. <i>Baryandra</i> (Begoniaceae)

Abstract: Begonia sect. Baryandra is distributed mainly in the Philippines with a few species in Borneo and New Guinea. Previous chromosome information of sect. Baryandra has restricted to ca. 16 species and their karyotypes have never been investigated. Here we report the cytological investigations of 26 species of sect. Baryandra, including five karyotype analyses that are the first report in sect. Baryandra, 24 species were reported cytologically for the first time, and two species were re-examined. Incorporating pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Although available cytological data of the section are still limited, a wide range of numbers (i.e., 2n=24-28, 28, 30, 36, 44, and 60) are reported. Among these numbers, 2n=28 (Legro and Doorenbos 1969) and 30 (Kono et al 2021a) are the most common numbers (Table 1), similar to sect. Baryandra (Kono et al 2021a) and sect.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although available cytological data of the section are still limited, a wide range of numbers (i.e., 2n=24-28, 28, 30, 36, 44, and 60) are reported. Among these numbers, 2n=28 (Legro and Doorenbos 1969) and 30 (Kono et al 2021a) are the most common numbers (Table 1), similar to sect. Baryandra (Kono et al 2021a) and sect.…”
Section: Discussionsupporting
confidence: 71%
“…While 2n=30 has been reported for both sections Haagea and Petermannia, this number is also known in other Asian Begonia sections, including Baryandra (Kono et al 2021a), Coelocentrum (Kono et al 2020), Diploclinium (Kono et al 2021b), Jackia Doorenbos 1969, Doorenbos et al 1998), and Reichenheimia (Sharma and Bhattacharyya 1957, Legro and Doorenbos 1973, Nakata et al 2003. However, karyotypic analyses showed 2n=30= 8m+ 22sm(st) in sections Baryandra (Kono et al 2021a) and Coelocentrum (Kono et al 2020), and 2n=30= 12m+ 18sm(st) 2sm in sect. Diploclinium (Kono et al 2021b).…”
mentioning
confidence: 88%
“…Although cytological studies available for the section are still limited, they show a great range (2n=18, 22, 24, 26, 30, 32, 36, 46, and 54) (Sarkar 1989). Early studies by Legro and Doorenbos (1969, 1971, 1973 suggested that 2n=22, 28, and 38 are the most common chromosome numbers in Begonia, while our recent study indicated that 2n=30 is also one of the most common numbers in Asian Begonia (Kono et al 2021). Among the four most common chromosome numbers (i.e., 2n=22, 28, 30 and 38), 2n=22 was reported previously in three sections: Diploclinium (White et al 1946, Legro and Doorenbos 1969, Doorenbos et al 1998, Parvibegonia (Legro and Doorenbos 1971), and Platycentrum (Sharma and Blattacharyya 1961, Legro and Doorenbos 1969, 1971, Peng and Chen 1990, 1991, Doorenbos et al 1998, Peng and Chiang 2000, Peng and Sue 2000, Tian et al 2002, Oginuma and Peng 2002, Nakata et al 2003, 2005, 2007, Ye et al 2004, Li et al 2005a,b, Kono et al 2012, Ding et al 2014, Peng et al 2005c, 2015b, 2n=28 in three sections: Baryandra (Nakamura et al 2013, 2015, Peng et al 2017b, Kono et al 2021, Petermannia (Piton 1962), and Reichenheimia (Li et al 2005a), 2n=30 in seven sections: Baryandra (Hugh...…”
Section: Discussionmentioning
confidence: 68%
“…In Asian Begonia, karyotypes have only been reported in four sections, i.e., sect. Baryandra (Kono et al 2021), Coelocentrum (Kono et al 2020), Diploclinium (Oginuma and Peng 2002), and Platycentrum (Oginuma and Peng 2002, Peng et al 2014c, 2015c. In sect.…”
Section: Karyotype Analyses and Chromosome Evolutionmentioning
confidence: 99%
See 1 more Smart Citation